Three-phase half-controlled boost converter operating in quasi-critical conduction mode - Morais, Douglas C. [UNESP]; Falcondes De Seixas, J. M. [UNESP]; Souza, Lucas C. [UNESP]; Lucianoe Silva, S. C.; Joao Junior, C. P. (Institute of Electrical and Electronics Engineers (IEEE), 2019)
AC-DC converters, which operate in discontinuous conduction mode, can be used as power factor correction. Operating with constant duty cycle, the control system presents low complexity, however, for low static voltage gains, the input current is not sinusoidal and has a high low order harmonic content, can going beyond the limits imposed by international norms and standards. As an alternative, an analysis and simulation of the three-phase semi-controlled boost rectifier in quasi-critical conduction mode is presented in this paper. This conduction mode ensures that the input current will follow a sinusoidal form, suppressing the use of sensors or current control meshes, providing greater robustness to converter. In addition, the quasi-critical mode maintains some advantages of the discontinuous operation mode, for example, the zero-current-switching during the turn-on of the switches, the simplicity of control system and the lower cost. In this configuration, the current stress in semiconductors are divided and, a single pulse is necessary for switch conduction. The results presented prove that occurs the power factor correction with harmonic current content reduction in low frequency.
Keywords: Power factor correction; Quasi-critical conduction mode; Three-phase boost converter